2013
DOI: 10.1179/1743132813y.0000000228
|View full text |Cite
|
Sign up to set email alerts
|

Combination of high-sensitivity C-reactive protein and homocysteine predicts the short-term outcomes of Chinese patients with acute ischemic stroke

Abstract: High-sensitivity C-reactive protein and HCY are independent predictors of short-term outcome and mortality after AIS. The combined model may provide additional general prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 68 publications
3
41
1
1
Order By: Relevance
“…This hypothesis has been observed in several clinical studies, with the high levels of serum Hcy as independent predictors for END for stroke patients [11, 14]. However, a recent study suggested conflicting results, demonstrating no association between elevated Hcy levels and functional outcome among elderly patients with acute cerebral infarction [15].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This hypothesis has been observed in several clinical studies, with the high levels of serum Hcy as independent predictors for END for stroke patients [11, 14]. However, a recent study suggested conflicting results, demonstrating no association between elevated Hcy levels and functional outcome among elderly patients with acute cerebral infarction [15].…”
Section: Discussionmentioning
confidence: 88%
“…The serum Hcy levels were found to be significantly higher in stroke patients than those of normal controls [11-13]. Also, the high levels of serum Hcy were independent predictors for early neurological deterioration (END) and death in multivariate analysis [14], with the prognostic accuracy of 0.83 and 0.82, respectively [11].…”
Section: Introductionmentioning
confidence: 99%
“…23 It has been reported that hs-CRP and homocysteine were independent predictors of short-term outcome and mortality after acute ischaemic stroke. 24 In contrast, others found that hs-CRP concentration could predict neither functional disability 3 months after stroke onset, 25 nor the severity of short-term functional disability. 26 We are planning a prospective study to determine the correlation between hs-CRP concentration and prognosis in patients with IEAO.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in untreated patients, SUA declined at 6 to 12 hours (P=0.298), 48 hours (P=0.010), and 90 days (P=0.030) after stroke onset [26]. When recorded on admission, different variables were associated with poor outcome in stroke patients, for example, HS-CRP [33], HCY [33], glucose [34], and NIHSS score [35]. In this study, we also found that the NIHSS score, FBG, and Hs-CRP remained significant outcome predictors.…”
Section: Discussionmentioning
confidence: 99%